Immunotherapy monotherapy for patients with recurrent nonmetastatic larynx cancer who refuse salvage total laryngectomy - Shires, Courtney Brooke; Sebelik, Merry E. (Frontiers in Oncology, 2025)
Objectives/HypothesisTotal laryngectomy has traditionally been recommended for patients with recurrent larynx cancer after radiation or chemoradiation. Some patients refuse salvage surgery. Historically, these patients have been placed on hospice or palliative chemotherapy. Immunotherapy has recently added another treatment modality to our armamentarium.Methods8 patients with recurrent larynx cancer declined salvage laryngectomy. They were started on immunotherapy alone. We recorded their demographics, initial cancer stage, initial cancer treatment, combined positive score (CPS) values, need for tracheostomy, addition of chemotherapy to their immunotherapy, and response to therapy.Results62.5% were African American, while 37.5% were Caucasian. Most had early (stage 1 or 2 disease) at the time of initial diagnosis. 75% had radiation alone as their initial treatment, while 25% had chemoradiation. All of these patients had high CPS scores. 37.5% progressed on 4 rounds of immunotherapy and are deceased. Chemotherapy was added to the regimen of 50% of the patients after poor response to immunotherapy. 75% of these patients are all still alive after 1 year of treatment. 75% of all patients needed tracheostomy while on salvage treatment. One patient (12.5%) has had a long-lasting positive response to immunotherapy alone.ConclusionsOur patients with nonmetastatic recurrent larynx cancer were found to have high CPS scores, which suggests favorable response to immunotherapy. Most patients with recurrent larynx cancer on immunotherapy required a tracheostomy. These patients had poor response on immunotherapy alone, but had prolonged survival with added chemotherapy. Salvage laryngectomy is the only curative option for these patients, but for those patients that refuse surgery, chemotherapy with immunotherapy has better results than immunotherapy alone. Our results reveal a possible clinical phenomenon, which needs to be confirmed by large sample studies.